Analisis Dampak Pengelolaan Dan Penggunaan Dana Desa Terhadap Pembangunan Daerah Berbasis Digital (Study Kasus Desa Rasau Kecamatan Torgamba Kabupaten Labuhanbatu Selatan) - Siti Amrina Hasibuan; Widya Ayu Harahap; Rizqy Fahmi; Juliana Nasution (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this research is to describe the impact of managing village funds in empowering villagers and to find out some of the enabling and hindering factors in managing village funds. This study used descriptive qualitative method. This research was carried out in one village in South Labuhanbatu Regency, namely Rasau Village, Torgamba District. The data obtained is the result of the field obtained through primary data collection such as observation, interviews, literature study, and secondary data collection such as existing documents or archives and also related written literature. The results of the study show that planning for the use of ADD in Rasau Village, Torgamba District, South Labuhanbatu Regency has been carried out in accordance with applicable regulations. This can be seen by the suitability between the planning carried out and the preparation of the activity plan stipulated in the Labuhanbatu Selatan Regent Regulation Number 7 of 2021 concerning procedures for allocating Village Funds. As for the results of the ADD in the village of Rasau, namely the construction of Water Pump, Drainage Rehabilitation, Construction of Street Lights, Concrete Roads, Rehab of River Crossing Boats, Construction of sports fields, construction of public toilets. Use of Village Fund Allocation In the village of Rasau, it can be seen that the recording of the use of ADD has been carried out properly. The use of ADD in the field of government operations as well as in the field of village development implementation has been well detailed. The allocation for its use is in accordance with existing regulations.